Effectiveness of Interactive Power-Point Learning Media Based on Guided Inquiry on Acid-Base Materials for Class XI SMA/MA - Desyana Anggraeni; Syamsi Aini (Jurnal Pendidikan dan Pembelajaran Kimia, 2022)
Abstract: The effectiveness of guided inquiry-based interactive power-point learning media on acid-base material for class XISMA/MA. This study aims to analyze the effectiveness of interactive power-point learning media based on guided inquiry on the acid-based topic on student learning outcomes at SMA Adabiah 2 Padang. This quasi-experimental study used a nonequivalent control-group design. The population consists of grade XI student of Adabiah 2 High School Padang in the 2021/2022 school year and samples were taken using purposive sampling technique. The research instrument was a multiple-choice test and the data were analyzed by n-gain test, normality test, homogeneity test and hypothesis testing by t-test. Based on data analysis, the experimental class n-gain was significantly higher than the control class with the medium category. To test the hypothesis obtained sig (2-tailed) 0.05 so that it indicates the hypothesis is accepted. It can be concluded that the use of interactive power-point learning media based on guided inquiry on acid-base material is effective in improving student learning outcomes at SMA Adabiah 2 Padang. Therefore, guided inquiry-based interactive power-point learning media on acid-base topic can be used for learning chemistry in the classroom.